Safe Water – Is it really Safe? - Lakhwani, Vinod M; Tiwari, Swati (Ushus Journal of Business Management, 2014)
Entering into the new field of business is not an easy go. One has to do market research, to identify the gap, to identify the product/service to be offered, and to target the right customer segment. After doing the required research, the next step is to make decisions on plant location, layout and then set up. Assessment of funds required for capital as well as revenue expenditure, procurement of machinery and other materials also take substantial amount of efforts. Searching for vendors and finalizing the right one are few other issues. After having worked successfully for more than 30 years in Bali in the field of sesame seeds and oil business Harsh was standing on a crossroad in 2011. Rising prices of sesame oil resulted in shift in customers’ taste and preferences towards refined oil. Moreover entry of big players at a large scale of operations and rise in price of raw material (sesame seeds) made survival tough. He had a number of options, one to continue with existing business at different scale of operations. Two, enter another business? Three, what business, Four, which place? The case talks about Harsh’s journey to new business, his choice and then the result.